The Political Economy of Labour Market Reforms - Duman, Özgün Sarımehmet. author. aut Link
XV, 247 p.
Keywords: Duman examines the transition from Keynesianism to monetarism by presenting an analysis of labour market reforms in Greece and Turkey - questioning the role of class struggle on the implementation process. She also scrutinises the influence of the global economic crisis and the execution of reform policies in these two countries.